2016
DOI: 10.1007/s10120-015-0589-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor analysis for involvement of resection margins in gastric and esophagogastric junction cancer: an Italian multicenter study

Abstract: Background Resection margin (RM) involvement is associated with negative prognosis after gastrectomy. Intraoperative frozen section (IFS) analysis allows radical resection to be achieved in a single operation but is timeconsuming and resource-consuming. The aim of this study was to assess risk factors associated with RM involvement to identify patients who would benefit from IFS analysis. Methods We retrospectively analyzed patients who underwent gastrectomy with curative intent for gastric or esophagogastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 29 publications
(60 reference statements)
5
41
1
2
Order By: Relevance
“…Die operative Strategie sollte generell so gewählt werden, dass zu Operationsbeginn die kritischen Resektionsränder geklärt werden, um das definitive Operationsverfahren festzulegen. Positive Schnittränder oral und aboral sollten intraoperativ durch einen Schnellschnitt möglichst vermieden werden [512,513]. Bei einem positiven intraoperativen Schnellschnitt sollte möglichst nachreseziert oder das OP-Verfahren gewechselt werden, wobei das Risiko der Eingriffserweiterung mit dem onkologischen Vorteil abgewogen werden sollte [475,512,514].…”
Section: Hintergrundunclassified
See 1 more Smart Citation
“…Die operative Strategie sollte generell so gewählt werden, dass zu Operationsbeginn die kritischen Resektionsränder geklärt werden, um das definitive Operationsverfahren festzulegen. Positive Schnittränder oral und aboral sollten intraoperativ durch einen Schnellschnitt möglichst vermieden werden [512,513]. Bei einem positiven intraoperativen Schnellschnitt sollte möglichst nachreseziert oder das OP-Verfahren gewechselt werden, wobei das Risiko der Eingriffserweiterung mit dem onkologischen Vorteil abgewogen werden sollte [475,512,514].…”
Section: Hintergrundunclassified
“…Die R1-Situation ist oft Ausdruck eines weit fortgeschrittenen Tumorstadiums und einer ungünstigen Tumorbiologie [510,513,514]. Meist erleiden Patienten mit R1-Situation einen systemischen Progress mit Fernmetastasen und kein Lokalrezidiv [510,512] Die Experten würdigen mit der Empfehlung für die perioperative Chemotherapie bzw.…”
Section: Hintergrundunclassified
“…We are observing an interesting phenomenon from a historical point of view; while 30 years ago the Japanese surgeons sustained an aggressive surgical approach to gastric cancer, which was subsequently accepted in the rest of the world, Western surgeons are actually more aggressive in this dissection nowadays than their Eastern counterpart. Other recently published papers, investigating Krukenberg tumors, margin infiltration and surgery in old patients, included as subgroup analysis number of patients with distant positive nodes, whose survival was not statistically different (when lymphadenectomy was done) from patients without nodal metastases in those basins (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…The demographic and clinicopathological characteristics of the patients are shown in Table 1 Previous studies have similarly reported that advanced T category, advanced N category, total gastrectomy, larger tumor, EGJ location, diffuse histology, and linitis plastica, which is also referred to as macroscopic type 4, [3,17,18] are risk factors for positive RM. On the basis of these studies, we chose candidate risk factors for preoperatively predicting clinicopathological features.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…However, the estimated risk would change depending on the actual secured margin distance. A multicenter Italian study reported that a RM distance of less than 2 cm was a risk factor for T1 tumors, and a RM distance of less than 3 cm was a risk factor for T2 to T4 Lauren intestinal pattern tumors [18]. The required margin distance should be evaluated in patients who have high-risk factors for positive RM in future studies.…”
Section: Patient Characteristicsmentioning
confidence: 99%